1995
DOI: 10.1111/j.1601-0825.1995.tb00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic periodontitis: possible lipid‐induced defect in tissue repair through alteration of macrophage phenotype and function

Abstract: BACKGROUND: Diabetes mellitus is a major health problem in the United States affecting approximately 13 million people. The five ‘classic’ complications which have historically been associated with the condition are microangiopathy, neuropathy, nephropathy, microvascu‐lar disease, and delayed wound healing. Recently, per‐iodontal disease (PD) has been declared the ‘sixth’ major complication of diabetes as diabetics demonstrate an increased incidence and severity of PD. The cellular and molecular basis for diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 151 publications
(111 reference statements)
2
40
0
9
Order By: Relevance
“…40 The elevation of serum lipids may also influence immune cell function by upregulating proinflammatory cytokines and superoxide production by PMNs and altering surface marker antigens of monocytes. 134 In the meanwhile, periodontitis can potentially induce insulin resistance by the overproduction of systemic proinflammatory cytokines, such as TNF-a, IL-1b, and IL-6. These cytokines will further ameliorate insulin insensitivity by destroying pancreatic b-cells, antagonizing insulin action, or altering intracellular insulin signaling through the NF-kB and c-Jun N-terminal kinase (JNK) axes.…”
Section: Alterations Of Periodontal Tissues With Diabetesmentioning
confidence: 99%
“…40 The elevation of serum lipids may also influence immune cell function by upregulating proinflammatory cytokines and superoxide production by PMNs and altering surface marker antigens of monocytes. 134 In the meanwhile, periodontitis can potentially induce insulin resistance by the overproduction of systemic proinflammatory cytokines, such as TNF-a, IL-1b, and IL-6. These cytokines will further ameliorate insulin insensitivity by destroying pancreatic b-cells, antagonizing insulin action, or altering intracellular insulin signaling through the NF-kB and c-Jun N-terminal kinase (JNK) axes.…”
Section: Alterations Of Periodontal Tissues With Diabetesmentioning
confidence: 99%
“…These include diabetes-induced alterations of immune cell phenotype and elevation of serum proinflammatory cytokine/lipid levels. [28293031323334] In recent times, some studies have demonstrated that periodontitis itself can produce these same alterations, and in the presence of diabetes, produces exacerbation of these detrimental changes. [343536373839]…”
Section: Introductionmentioning
confidence: 99%
“…3 The chronic hyperglycemia of poorly controlled diabetes mellitus induces events that promote structural changes in various tissues and are associated with problems in wound healing and a greater susceptibility to infections. [4][5][6] Actinomycosis mimics different diseases and exhibits different symptoms, a fact that makes its diagnosis difficult. 3 Most commonly, it presents as a slowly progressive, indolent, indurated infiltration with multiple abscesses, fistulas, and sinuses.…”
mentioning
confidence: 99%